THE CORRELATION BETWEEN STUDENTS’ WRITING ABILITY AND THEIR VOCABULARY MASTERY - Dzur Rif'ah Mahmudah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
This research aimed to find out the correlation between students’ writing ability and their vocabulary mastery of the eighth-grade students SMP Handayani Sungguminasa Gowa. The problem statement of the research was, “Is there any correlation between students’ writing ability and their vocabulary mastery?” The research used a Descriptive Research, the instrument of this study tested, namely writing ability (in terms of rewriting of the story in the film) test and vocabulary mastery test. The population of this research is to the eighth-grade students of SMP Handayani Sungguminasa Gowa which consists of 28 students, all of them were the sample. Therefore, this research used cluster sampling. The result of the data analysis shows that the students’ writing ability (in terms of rewriting of the story in the film) stated in 60.00 of the mean score, where their vocabulary mastery test stated 61.00 of the mean score. Coefficient correlation between both variables shows that there is a significant correlation between students writing ability and their vocabulary mastery, it has lies between 0,600 - 0,800 which is categorized as substantial.Keywords: correlation, writing, vocabulary, ability